Effect of welding parameters on mechanical properties and microstructure of friction stir welded brass joints - BİLİCİ, MUSTAFA KEMAL (EDP SCIENCES S A, 2019)
Friction stir welding is a method developed for the welding of high-alloy aluminum materials which are difficult to combine with conventional welding methods. Friction stir welding of MS 63 (brass) plates used different tools (tapered cylindrical, tapered threaded cylindrical), tool rotational speeds (1040, 1500, 2080 rpm) and traverse speeds (30,45,75,113 mm.min(-1)). Tensile, bending, radiography and microstructure tests were carried out to determine the mechanical properties of brass plates joined by friction stir welding technique. Microstructure characterization studies were based on optical microscope and SEM analysis techniques. In addition, after joining operations, radiographs were taken to see the internal structure failure. Brass sheets were successfully joined to the forehead in the macrostructure study. In the evaluation of the microstructure, it was determined that there were four regions of base metal, thermomechanically affected zone (TMEB), heat-affected zone (HAZ) and stir zone. In both welding tools, the weld strength increased with increasing tool rotation speed. The particles in the stir zone are reduced by increasing of the tool rotation speed. Given the strength and % elongation values, the highest weld strength was achieved with tapered pin tool with a tool rotation speed of 1040 rpm and a tool feed speed of 113 min(-1).
Keywords: friction stir welding; brass; microstructure; mechanical properties; ALUMINUM-ALLOY; SPEED; BEHAVIOR